HERBAL NANOSUSPENSION: IN VITRO CANCER STUDY AGAINST DIFFERENT CELL LINES - MM, MITHRA; K, KRISHNAKUMAR; K NAIR, SMITHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Herbal formulations marketed in India for many years providing its therapeutic benefits in health problems. Medicinal plants or their phytoconstituents are less toxic and free from side effects than synthetic drugs. However, formulation aspects of these phytoconstituents are limited due to its low solubility. Nanotechnology is a promising technique to increase the solubility of herbal drugs. This will lead to a subsequent reduction in drug dose. Nanoformulations such as nanosuspension increase the solubility of poorly soluble drugs and also have good targeting effects on different cells. The efficacy of herbal nanosuspensions evaluated using different cell lines. Here, hepatocellular carcinoma cell line (SMMC-7721), human prostate cancer cell line, human myelogenous leukemia cell line, human epithelial cell line, human breast cancer cell lines (4T1, MCF-7, and MDA-MB-453), carcinomic human alveolar basal epithelial cell line (A549), human umbilical vein endothelial cell line, human colorectal adenocarcinoma cell line (HT-29), and human epithelial carcinoma cell line (HeLa) are used in the evaluation procedures. In vitro assays help in the determination of the dose range of drugs for the activity. The present review highlights the in vitro cancer studies of herbal nanosuspensions using different cell lines.